2011
DOI: 10.1371/journal.pone.0020333
|View full text |Cite
|
Sign up to set email alerts
|

IL-17RA Is Required for CCL2 Expression, Macrophage Recruitment, and Emphysema in Response to Cigarette Smoke

Abstract: Chronic Obstructive Pulmonary Disease (COPD) is characterized by airspace enlargement and peribronchial lymphoid follicles; however, the immunological mechanisms leading to these pathologic changes remain undefined. Here we show that cigarette smoke is a selective adjuvant that augments in vitro and in vivo Th17, but not Th1, cell differentiation via the aryl hydrocarbon receptor. Smoke exposed IL-17RA−/− mice failed to induce CCL2 and MMP12 compared to WT mice. Remarkably, in contrast to WT mice, IL-17RA−/− m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
143
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(147 citation statements)
references
References 37 publications
4
143
0
Order By: Relevance
“…It is therefore conceivable that IL-22 production is promoted by direct effects on T-cells of AHR agonists present in cigarette smoke. This is supported by recent findings in the mouse [34] and in humans [35], demonstrating that addition of cigarette smoke extract to T-cells undergoing Th17 differentiation augments the percentage of IL-22 producing cells via an AHR-dependent mechanism. Future studies should also examine a group of smokers with normal lung function to see if these results can be confirmed in this control group.…”
Section: Effects Of Smoking On Cytokine Expressionsupporting
confidence: 77%
“…It is therefore conceivable that IL-22 production is promoted by direct effects on T-cells of AHR agonists present in cigarette smoke. This is supported by recent findings in the mouse [34] and in humans [35], demonstrating that addition of cigarette smoke extract to T-cells undergoing Th17 differentiation augments the percentage of IL-22 producing cells via an AHR-dependent mechanism. Future studies should also examine a group of smokers with normal lung function to see if these results can be confirmed in this control group.…”
Section: Effects Of Smoking On Cytokine Expressionsupporting
confidence: 77%
“…More recent reports unraveled beneficial effects of SFN in experimental chronic obstructive pulmonary disease (COPD) (28,53). SFN reduced pulmonary inflammation in COPD, a condition associated with Th17 responses (54,55). The aim of our study was to elucidate the immunoregulatory capabilities of SFN in terms of affected immune cells and underlying molecular mechanisms during T cell-mediated autoimmune responses.…”
Section: Sfn Treatment Inhibits Il23a/il12b Expression and Th17/th1 Dmentioning
confidence: 99%
“…The effect of rhMMP-12 was also examined on human alveolar type II-like epithelial cells (A549) and on human bronchial epithelial cells (BEAS-2B), showing that rhMMP-12 enhances the release of several chemokines by A549 cells, in particular, monocyte chemoattractant protein-1 (MCP-1)/CCL2, growth-related oncogene-a (GRO-a)/CXCL1, and IL-8/CXCL8 (Le Quement et al, 2008). In their study Chen and colleagues have partially elucidated the immunological mechanisms leading to pathologic changes associated to COPD (Chen et al, 2011b). They have shown that cigarette smoke is a powerful T helper 17 [Th17] cells adjuvant and that interleukin 17A receptor signaling is required for chemokine expression necessary for MMP-12 induction and tissue emphysema (Chen et al, 2011b).…”
Section: Spinal Cord Injury (Sci)mentioning
confidence: 99%
“…In their study Chen and colleagues have partially elucidated the immunological mechanisms leading to pathologic changes associated to COPD (Chen et al, 2011b). They have shown that cigarette smoke is a powerful T helper 17 [Th17] cells adjuvant and that interleukin 17A receptor signaling is required for chemokine expression necessary for MMP-12 induction and tissue emphysema (Chen et al, 2011b).…”
Section: Spinal Cord Injury (Sci)mentioning
confidence: 99%